Melatonin abrogates nonylphenol‐induced testicular dysfunction in Wistar rats. (10th August 2016) - Tabassum, H.; Parvez, S.; Raisuddin, S.
Summary: Endocrine‐disrupting chemicals present in the environment can bring about hormonal imbalance and be potentially harmful to the human health. Alkylphenols are omnipresent in the environment as they are constituents of several products. The aim of this study was to evaluate the effect of exogenous melatonin treatment on nonylphenol (NP)‐induced oxidative stress and testicular toxicity in Wistar rats using biochemical and histopathological parameters. The oxidative stress biomarkers, activities of enzymatic and non‐enzymatic antioxidants and histopathological evaluation were performed in testicular tissues. NP caused elevated TBARS levels and marked alteration of both nonenzymatic and enzymatic biomarkers. Furthermore, severe histopathological alterations were observed in the testis of NP‐exposed animals as compared with that of the control rats. Melatonin supplementation ameliorated the alterations in these biochemical and histopathological variables in rats. In conclusion, our results demonstrated that melatonin through its antioxidant activity effectively protected against the NP‐induced testicular toxicity.